Larger Sensitivity of Arctic Precipitation Phase to Aerosol than Greenhouse Gas Forcing. Issue 23 (8th December 2020) - Pan, Shifeng; Dou, Tingfeng; Lin, Lei; Yang, Jiao; Zhang, Feng; Duan, Mingkeng; Zhao, Chuanfeng; Liao, Hong; Xiao, Cunde
Abstract: The sensitivity of the Arctic precipitation phases (solid and liquid) to the forcings from greenhouse gases (GHGs) and aerosols over 2016–2080 was investigated by using the Community Earth System Model Version 1. Results show that the warming caused by the two forcings results in an increasing trend in total precipitation and a solid‐to‐liquid precipitation transition in the Arctic. Under RCP8.5 scenario, the increased rate of Arctic mean precipitation with global warming forced by aerosol reduction (7.7%/°C) is twice greater than that by increased GHG emission (3.5%/°C). The sensitivity of rainfall to precipitation ratio (RPR) to various forcings is much higher than that of total precipitation in the Arctic. The increased rate of RPR due to global aerosol forcing (8.4%/°C) is approximately 3 times that due to GHG forcing (2.9%/°C) in the Arctic, the differences even larger over Greenland and the eastern Arctic Ocean, resulting in more rainfall in these areas. Plain Language Summary: The precipitation phase is extremely sensitive to temperature changes, especially in the Arctic. Solid and liquid precipitation have almost the opposite effect on the ground energy budget. The changes in precipitation phase can greatly affect snow and ice mass balance, regulating the regional hydrological cycle. The transition from solid precipitation to liquid precipitation can even promote carbon release over the permafrost through changing the rate of snow melting. We evaluated the impacts of the two most important anthropogenic forcing agents (greenhouse gases [GHGs] and aerosols) on the changes of precipitation phases in the Arctic using a state‐of‐the‐art Earth system model. We found that the warming forced by global aerosol reduction and increased GHG emission leads to a solid‐to‐liquid precipitation transition and therefore more rainfall events in the Arctic. Under RCP8.5 scenario, the sensitivity of Arctic precipitation phase to global aerosol forcing is approximately 3 times that to the GHG forcing, and the most sensitive phase changes of Arctic precipitation to the aerosol forcing are observed in Greenland and the eastern Arctic Ocean. Understanding the impact of human activities on the changes in the Arctic precipitation phase will help formulate reasonable emission reduction policies and better adapt to the rapid Arctic climate changes in the future. Key Points: Warming forced by global aerosol reduction and increased GHG emission leads to a solid‐to‐liquid precipitation transition in the Arctic The sensitivity of Arctic precipitation phase to the aerosol forcing is approximately three times that to the GHG forcing The most sensitive phase changes of Arctic precipitation to the aerosol forcing are observed in Greenland and the eastern Arctic Ocean